Предмет: Алгебра,
автор: marizdorova
Помогите решить логарифмическое уравнение
Приложения:
Ответы
Автор ответа:
0
Решение
log2 ((4x-1)/3) + log2 x = 0
ОДЗ: [ > 0
log2 [ ((4x-1)/3) * (x) ] = 0
((4x-1)/3) * x =2^0
(4x^2 -x) / 3 = 1
4x^2 -x -3 = 0
d = 1 + 4*4*3 = 49
x1 = (1 - 7) /8
x1 = -3/4 не удовлетворяет ОДЗ
x2 = (1 + 7)/4
x2 = 2
Ответ: х = 2
log2 ((4x-1)/3) + log2 x = 0
ОДЗ: [ > 0
log2 [ ((4x-1)/3) * (x) ] = 0
((4x-1)/3) * x =2^0
(4x^2 -x) / 3 = 1
4x^2 -x -3 = 0
d = 1 + 4*4*3 = 49
x1 = (1 - 7) /8
x1 = -3/4 не удовлетворяет ОДЗ
x2 = (1 + 7)/4
x2 = 2
Ответ: х = 2
Похожие вопросы
Предмет: Музыка,
автор: dubnastya0704
Предмет: Геометрия,
автор: dzamolamarov
Предмет: Химия,
автор: Аноним
Предмет: Математика,
автор: ginaylo82